## 每週問題 March 18, 2013

Let $A$ and $B$ be $n\times n$ matrices. Prove the following statements.
(a) If $AB=BA$, then $e^{A+B}=e^Ae^B$.
(b) If $e^{(A+B)t}=e^{At}e^{Bt}$ for all $t$, then $AB=BA$.

(a) 可交換矩陣，即 $AB=BA$，滿足二項式定理 $(A+B)^m=\sum_{k=0}^m\binom{m}{k}A^{k}B^{m-k}$。使用 $e^A$ 的定義式，推導過程如下：

\begin{aligned}\displaystyle e^{A+B}&=\sum_{m=0}^\infty\frac{(A+B)^m}{m!}=\sum_{m=0}^\infty\sum_{k=0}^m\frac{\binom{m}{k}A^kB^{m-k}}{m!}\\ &=\sum_{k=0}^\infty\sum_{m=k}^\infty\frac{A^k}{k!}\frac{B^{m-k}}{(m-k)!}= \sum_{k=0}^\infty\sum_{l=0}^\infty\frac{A^k}{k!}\frac{B^{l}}{l!}\\ &=e^Ae^B. \end{aligned}

(b) 考慮 $e^{(A+B)t}$$e^{At}e^{Bt}$ 的展開式：

\begin{aligned}\displaystyle e^{(A+B)t}&=I+(A+B)t+(A+B)^2\frac{t^2}{2}+\cdots\\ &=I+(A+B)t+(A^2+AB+BA+B^2)\frac{t^2}{2}+\cdots \end{aligned}

\begin{aligned}\displaystyle e^{At}e^{Bt}&=\left(I+At+A^2\frac{t^2}{2}+\cdots\right)\left(I+Bt+B^2\frac{t^2}{2}+\cdots\right)\\ &=I+(A+B)t+(A^2+2AB+B^2)\frac{t^2}{2}+\cdots.\end{aligned}

$A^2+AB+BA+B^2=A^2+2AB+B^2$

$AB=BA$

PowSol-March-18-13